A Comparison of Thoracolumbar Intervertebral Disc Extrusion in French Bulldogs and Dachshunds and Association With Congenital Vertebral Anomalies. Issue 3 (16th January 2014) - Aikawa, Takeshi; Shibata, Mitsuhiro; Asano, Moe; Hara, Yasushi; Tagawa, Masahiro; Orima, Hiromitsu
<x xml:space="preserve">Abstract</x> Objectives To compare data for French Bulldogs and Dachshunds that had hemilaminectomy for thoracolumbar intervertebral disc extrusion (T‐L IVDE) by 1 surgeon and to evaluate the association between IVDE and congenital vertebral anomalies. Design Retrospective case series. Animals French Bulldogs (n = 47) and 671 Dachshunds. Methods Age, gender, vertebral anomaly, kyphosis/kyphoscoliosis, IVDE site, non‐recovery and progressive hemorrhagic myelomalacia development from grade 5 (paraplegia without deep nociception) were compared between the 2 breeds. Results French Bulldogs were significantly younger (P = .00001), more likely to be male (P = .023), and more likely to have a congenital vertebral anomaly and kyphosis/kyphoscoliosis (P < .00001) than Dachshunds. The frequencies of French Bulldogs with IVDE within typical sites (T11‐L3) were significantly lower (P = .0005) and within caudal sites (L3‐L7) significantly higher (P = .0001) compared with Dachshunds. None of the French Bulldogs had IVDE within the kyphotic/kyphoscoliotic segment. The frequency of lumbar IVDE (L1‐L5) in French Bulldogs with kyphosis/kyphoscoliosis was significantly higher (P = .003) compared with French Bulldogs without kyphosis/kyphoscoliosis. In grade 5 dogs, the risk of developing progressive hemorrhagic myelomalacia in French Bulldogs was significantly higher (P = .03) than in Dachshunds. Conclusion The distribution of IVDE site in French Bulldogs within the thoracolumbar and lumbar spine was different from Dachshunds. IVDE sites were not located at the sites of vertebral anomaly. French Bulldogs appeared to have T‐L IVDE at younger ages, with higher male predisposition and higher risk of developing progressive hemorrhagic myelomalacia from grade 5 compared with Dachshunds.